Intra- and Interpersonal Factors in Adolescence Predicting Loneliness among Young Adults with Visual Impairments. (January 2019) - Veerman, Linda; Heppe, Eline; Gold, Deborah; Kef, Sabina
Introduction: Youths with visual impairments (i.e., blindness or low vision) experience difficulties with forming and maintaining social relationships with peers. These difficulties challenge their psychosocial functioning and put them at risk of being lonelier later in life. The study's primary goal was to investigate how intra- and interpersonal factors during adolescence influence Loneliness in young adulthood. Methods: Analyses were conducted on data from a national data set. Participants ( N = 96) were interviewed at two different time points. General linear regression and mediation analyses were used to examine the role of social competence, personality, and satisfaction with social support, measured at mean age 17.83, and on Loneliness measured at mean age 23.45. Results: Analyses showed that adolescents with visual impairments who were more emotionally stable and had higher social competence during adolescence were less lonely later in life. In addition, the results showed that emotionally unstable adolescents reported lower social competence and, therefore, were lonelier in young adulthood. Discussion: These findings indicate that factors connected to Loneliness in young adulthood include people's personality traits and their level of social competence at a younger age. Implications for practitioners: Knowing the underlying causes of an individual's Loneliness assists practitioners in selecting what type of intervention would be suitable for addressing these issues. Those with low social skills benefit more from social skills training and those with negative biases of their own functioning profit more from interventions based on cognitive approaches. Screening methods could be used in order to determine these underlying issues and personality structure, before assigning persons to specific interventions.